A case report on Bardet–Biedl syndrome with disease-causing variant Bardet–Biedl syndrome 1: De novo diabetes mellitus - Korrapati, Rakesh; Krovvidi, Sahithi; Mupparaju, Jaya Sai; Chundu, Umesh Chandra; Meduri, Saiteja; Tiriveedhi, Sreeram (Indian Journal of Case Reports, 2025)
Diabetes mellitus (DM), particularly type 2 diabetes, is demonstrated as one of the common complications and/or a secondary feature in Bardet–Biedl syndrome (BBS) individuals. This case report presents the case of a 15-year-old boy from Andhra Pradesh, India, with BBS, showing polyuria, polydipsia, and elevated blood sugar (400 mg/dL). The patient was diagnosed with BBS at age 11 based on truncal obesity, low intellectual quotient, polydactyly, hypogonadism, and next-generation sequencing. The genetic analysis revealed a homozygous state due to c.195+1G>c in intron 10 of the FBN3 gene that is associated with autosomal recessive BBS1. On examination, his random plasma glucose (466 mg/dL) and glycated hemoglobin (HbA1C) (>15.0%) were elevated. Consequently, he was diagnosed with a case of de novo DM BBS. Ophthalmic evaluation indicated retinitis pigmentosa sine pigmento. Insulin therapy showed improvement in the condition of the patient. The patient was counseled on low-caloric food, physical activity, and regular follow-ups in addition to genetic counseling. The report emphasizes the importance of thorough evaluation following diagnosis to gauge the extent of the disease to prevent complications such as diabetes and renal impairment.